معوقات تطبيق المعيار الدولي لإعداد التقارير المالية (IFRS 9) وأثرها على جودة معلومات التقارير المالية - محمد حويليد.اسماعيل عيسى; محمد حسن أ. مصطفى أحمد (Aljameai, 2025)
المستخلص: هدفت الدراسة إلى التعرف على معوقات تطبيق المعيار الدولي لإعداد التقارير المالية (IFRS 9) وأثرها على جودة معلومات التقارير المالية في المصارف التجارية الليبية. ولتحقيق هذا الهدف، اعتمدت الدراسة على المنهج الوصفي التحليلي، واستخدمت استمارة الاستبيان كأداة رئيسة لجمع البيانات، وقد تم توزيعها على عينة طبقية عشوائية من موظفي إدارات المحاسبة والمراجعة الداخلية بالمصارف التجارية الليبية الواقعة في المنطقة الشرقية، إضافة إلى المراجعين الخارجيين المقيدين لدى مصرف ليبيا المركزي والعاملين في الرقابة المصرفية. كما اعتمدت الدراسة على أساليب الإحصاء الوصفي والاستنتاجي لتحليل البيانات، وتم اختبار فرضيات الدراسة باستخدام اختبار الانحدار الخطي البسيط (Simple Linear Regression)، واختبار (One-Sample T-Test)، لعينة واحدة، واختبار (T-Test) لعينتين مستقلتين. وتوصلت نتائج الدراسة إلى وجود أثر سلبي ذو دلالة إحصائية لمعوقات تطبيق المعيار (IFRS 9) على جودة معلومات التقارير المالية في المصارف التجارية الليبية، كما أظهرت النتائج أن هذه المعوقات تؤثر سلبًا وبصورة معنوية على أبعاد جودة المعلومات المالية المتمثلة في الملاءمة، والموثوقية، وقابلية المقارنة، والقابلية للفهم. كذلك أظهرت الدراسة عدم وجود فروق ذات دلالة إحصائية بين معدي ومستخدمي المعلومات المحاسبية فيما يتعلق بإدراك معوقات تطبيق المعيار وأثرها على جودة التقارير المالية. وبناءً على هذه النتائج، أوصت الدراسة بضرورة تطوير البنية التنظيمية والتقنية للمصارف التجارية الليبية، وتعزيز كفاءة الكوادر، ودعم نظم المعلومات المحاسبية، بما يسهم في تحسين جودة المعلومات، وضمان التطبيق الفعال لمعيار (IFRS 9). Abstract: This study aims to identify the obstacles to the implementation of International Financial Reporting Standard (IFRS 9) and to examine their impact on the quality of financial reporting information in Libyan commercial banks. To achieve this objective, the study adopted a descriptive–analytical approach and employed a questionnaire as the primary instrument for data collection. The questionnaire was distributed to a stratified random sample comprising employees of accounting and internal audit departments in Libyan commercial banks located in the eastern region, in addition to external auditors registered with the Central Bank of Libya and professionals working in banking supervision. The study relied on descriptive and inferential statistical techniques to analyze the data, and the research hypotheses were tested using Simple Linear Regression, the One-Sample T-Test, and the Independent Samples T-Test. The results revealed a statistically significant negative effect of the obstacles to IFRS 9 implementation on the quality of financial reporting information in Libyan commercial banks. Furthermore, the findings indicated that these obstacles have a significant adverse impact on the main dimensions of information quality, namely relevance, reliability, comparability, and understandability. The study also found no statistically significant differences between preparers and users of accounting information regarding their perceptions of IFRS 9 implementation obstacles and their impact on the quality of financial reporting. Based on these findings, the study recommends developing the organizational and technological infrastructure of Libyan commercial banks, enhancing staff competencies, and supporting accounting information systems, in order to improve information quality and ensure the effective implementation of IFRS 9.